Local Migration Regimes in Rural Areas: The Example of Refugee Reception in Saxony, Germany - Hanne Schneider (Comparative Population Studies, 2022)
The reception of asylum seekers has challenged municipalities and their populations across Europe in recent years: Many rural villages and small and mid-sized towns had little prior experience with large numbers of asylum seekers. The housing of refugees constitutes one of the most controversial arenas and challenges for local communities within the reception process.